The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijerph20095663
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Paternal Epigenetic Inheritance

Abstract: Cannabis is the most widely used illicit drug in Western counties and its abuse is particularly high in male adolescents and young adults. Its main psychotropic component, the cannabinoid delta-9-tetrahydrocannabinol (Δ9-THC), interferes in the endogenous endocannabinoid system. This signaling system is involved in the control of many biological activities, including the formation of high-quality male gametes. Direct adverse effects of Δ9-THC in male reproduction are well known in both animal models and humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Data from studies on rodents have shown that preconcpeptional paternal exposure to delta-9-tetrahydrocannabinol (∆9-THC), the most active cannabinoid, leads to deficits in cholinergic synaptic function in offspring, along with abnormalities in locomotor activity, impaired cognitive function, and long-lasting neurobehavioral effects. Additionally, exposure to ∆9-THC during adolescence in rats has been found to cause intergenerational effects on DNA methylation status in the nucleus accumbens (NAc) [158].…”
Section: Transgenerational Consequences Of Epigenetic Changes In Sper...mentioning
confidence: 99%
“…Data from studies on rodents have shown that preconcpeptional paternal exposure to delta-9-tetrahydrocannabinol (∆9-THC), the most active cannabinoid, leads to deficits in cholinergic synaptic function in offspring, along with abnormalities in locomotor activity, impaired cognitive function, and long-lasting neurobehavioral effects. Additionally, exposure to ∆9-THC during adolescence in rats has been found to cause intergenerational effects on DNA methylation status in the nucleus accumbens (NAc) [158].…”
Section: Transgenerational Consequences Of Epigenetic Changes In Sper...mentioning
confidence: 99%
“…In Western countries, the recreational use of illicit drugs, such as cannabis, is common mainly in male adolescents and young men, with several negative life outcomes like depression, substance use disorders, and psychosis, as well as social impacts [ 27 , 28 ]. In this respect, adolescence is a critical period for the completion of several developmental processes, including neurodevelopment and reproductive functions [ 15 , 28 , 29 ]. Hence, cannabis use during adolescence might epigenetically impact brain health, and thus deserves attention.…”
mentioning
confidence: 99%